Effects of bacterial wilt on community composition and diversity of culturable endophytic fungi in Alpinia galanga - Liu, Jiahui; Wu, Yuanyuan; Lin, Jinru; Xie, Mengxia; Chen, Likai; Wang, Liguo (Frontiers in Microbiology, 2025)
Alpinia galanga Willd is a perennial herbaceous plant that usually has a stable microflora living in the inter-root and stem and leaf tissues, which assists the host in normal growth and development. The bacterial wilt disease investigated in A. galanga planting bases is a novel soil-borne disease caused by the pathogenic bacterium Ralstonia solanacearum (Smith) Yabuuchi et al., which disrupts the A. galanga-microbe-soil microecological balance. For this reason, it is important to study the changes in endophytic fungal community growth and diversity in healthy and diseased A. galanga, and to mine the active endophytic fungal resources in order to lay the foundation for exploring the functional microbial communities for artificial synthesis. From 685 endophytic fungi strains isolated from healthy (HDK_J) and diseased (HDK_B) A. galanga stems/leaves, 27 species were identified in HDK_J and 8 in HDK_B (belonging to 3 Phyla, 6 Classes, 13 Families). HDK_B’s fungal relative abundance (RA) was only 38.93% of HDK J’s, indicating significantly lower composition/abundance. While species in stems and leaves were identical within health groups, leaf RA exceeded stems by 124.23% in HDK_J and 78.23% in HDK_B. The RA of HDK_J leaves was 78.08% higher than that of stems. All diversity indices for HDK_J were higher than those for HDK_B, with significant differences. The phylogenetic trees revealed four major branches of endophytic fungi species in HDK_J, and especially, there were many long development branches under the Ascomycota. In contrast, the phylogenetic tree for HDK_B showed only one major branch (Ascomycota) with few sub-branches. The bacterial wilt significantly affected the composition and RA of endophytic fungi in A. galanga. The diversity indices showed a decreasing trend in A. galanga after being infected by R. solanacearum. The dominant species were changed. The parts of sensitive endophytic fungi had disappeared. This result will be helpful for studies on the relationship between the artificial minimal microbial community and the role of the host, as well as for studies on synthetic microbiomics.